Laboratory and field measurements of enantiomeric monoterpene emissions as a function of chemotype, light and temperature (BIOGEOSCIENCES, 2014)
Plants emit significant amounts of monoterpenes into the earth's atmosphere, where they react rapidly to form a multitude of gas phase species and particles. Many monoterpenes exist in mirror-image forms or enantiomers. In this study the enantiomeric monoterpene profile for several representative plants (Quercus ilex L., Rosmarinus officinalis L., and Pinus halepensis Mill.) was investigated as a function of chemotype, light and temperature both in the laboratory and in the field. Analysis of enantiomeric monoterpenes from 19 Quercus ilex individuals from Southern France and Spain revealed four regiospecific chemotypes (genetically fixed emission patterns). In agreement with previous work, only Quercus ilex emissions increased strongly with light. However, for all three plant species no consistent enantiomeric variation was observed as a function of light, and the enantiomeric ratio of alpha-pinene was found to vary by less than 20% from 100 and 1000 mu mol m(-2) s(-1) PAR (photosynthetically active radiation). The rate of monoterpene emission increased with temperature from all three plant species, but little variation in the enantiomeric distribution of alpha-pinene was observed with temperature. There was more enantiomeric variability between individuals of the same species than could be induced by either light or temperature. Field measurements of alpha-pinene enantiomer mixing ratios in the air, taken at a Quercus ilex forest in Southern France, and several other previously reported field enantiomeric ratio diel cycle profiles are compared. All show smoothly varying diel cycles (some positive and some negative) even over changing wind directions. This is surprising in comparison with variations of enantiomeric emission patterns shown by individuals of the same species.
APS